Tracing Enriched Mantle Components along the Gakkel Ridge, Arctic Ocean - Nguyen, Nam Hien 1985- (2013)
Mid-ocean ridge basalts (MORBs) along the Gakkel Ridge in the Arctic Eurasian basin have varying levels of trace element enrichment. The purpose of this research is to determine the extent to which the trace element enrichment of basalts along the Gakkel Ridge is influenced by magmatic differentiation processes or mantle heterogeneity. This was accomplished by calculating the effects of magmatic differentiation on basalt trace element ratios and by defining the compositions of mantle components in the mantle along Gakkel Ridge and interpreting their origins, scales, and distribution. Electron microprobe and laser-ablation inductively-coupled-plasma mass-spectrometer (LA-ICP-MS) instruments were used to analyze major element and trace element concentration data in glass chips of basalt samples dredged from the Gakkel Ridge. As a consequence of Gakkel Ridge’s ultraslow spreading rate, fractional crystallization has only a minimal effect on trace element ratios of Gakkel Ridge MORBs. Trace elements plotted on ternary plots reveal four main aspects about the nature of the enriched component along Gakkel Ridge: 1) Sparsely Magmatic Zone (SMZ) and Eastern Volcanic Zone (EVZ) basalt trace element data plot along a two-component mixing line trending between a depleted MORB mantle (DMM) composition and an average Mid-Atlantic Ridge enriched-MORB (MAR E-MORB) composition. This mixing line is separate from the mixing line on which the Western Volcanic Zone (WVZ) trace element data plot, which trends between the DMM and the high-K2O Central Lena Trough (CLT) source; 2) The level of enrichment in MORB samples of the SMZ and EVZ varies from being relatively similar across a span of 97 km in the EVZ at 31-47°E, to changing significantly between individual dredging stations in the SMZ at 13°E, 19°E, and in the EVZ at 55°E. This shows that the size and distribution of enriched reservoirs drastically vary; 3) Trace elements indicate that the main enriched source of the EVZ and SMZ basalts resemble MAR E-MORB source mantle and is not continental in origin; and 4) At least one additional enriched source exists along Gakkel Ridge, as evidenced by the chemical signature in the EVZ at 55°E, which shows at least three different mixing component compositions. Earth and Atmospheric Sciences, Department of